Умови сценарного договору - Аврамова, О. Є.; Михайлова, Карина Олександрівна (НТУ "ХПІ", 2013)
The article deals with the issues practical compilation scenario of the contract. The characteristic of screen writing contract, in particular, as duplex, written, or real consensual agreement.
Keywords: сценарій; сюжет; кінофільм; серіал телевізійний; власність інтелектуальна